2020
DOI: 10.1093/mnras/staa459
|View full text |Cite
|
Sign up to set email alerts
|

Interacting galaxies in the IllustrisTNG simulations – II: star formation in the post-merger stage

Abstract: Galaxy mergers are a major evolutionary transformation whose effects are borne out by a plethora of observations and numerical simulations. However, most previous simulations have used idealised, isolated, binary mergers and there has not been significant progress on studying statistical samples of galaxy mergers in large cosmological simulations. We present a sample of 27,691 post-merger (PM) galaxies (0 ≤ z ≤ 1) identified from IllustrisTNG: a cosmological, large box, magneto-hydrodynamical simulation suite.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 101 publications
(182 reference statements)
5
77
3
Order By: Relevance
“…The distributions of SFR fibre estimated in the SF-DPS galaxies peak between 2 and 10 M yr −1 and is about a factor of 2 larger than for the NBCS. In numerical simulations, Hani et al (2020) found an SFR enhancement of a factor two in 10.0 ≤ log(M * /M ) ≤ 11.4 SF post-merger galaxies.…”
Section: A171 Page 21 Of 31mentioning
confidence: 91%
See 2 more Smart Citations
“…The distributions of SFR fibre estimated in the SF-DPS galaxies peak between 2 and 10 M yr −1 and is about a factor of 2 larger than for the NBCS. In numerical simulations, Hani et al (2020) found an SFR enhancement of a factor two in 10.0 ≤ log(M * /M ) ≤ 11.4 SF post-merger galaxies.…”
Section: A171 Page 21 Of 31mentioning
confidence: 91%
“…Di Matteo et al 2007). However, Hani et al (2020) found that strong enhancements of SFR are dominated by major mergers. They estimated that a starburst of 50 M yr −1 has four times higher chances to occur in a major merger than in a minor merger.…”
Section: Minor Versus Major Mergersmentioning
confidence: 97%
See 1 more Smart Citation
“…A summary of current estimates in the literature for the timescales on which different physical processes regulate the growth of galaxies. These timescales are estimated from theoretical models and simulations of galaxy evolution, with the corresponding references listed in Appendix C. The different colours highlight the different scales and types of physical processes, ranging from processes regulating the creation and destruction of GMCs (purple; Leitherer et al 1999;Tan 2000;Tasker 2011;Faucher-Giguère 2018;Benincasa et al 2019), dynamical processes within galaxies (green; Krumholz & Burkert 2010;Hopkins et al 2014;Forbes et al 2014b;Semenov et al 2017, the cycling of baryons in the ISM and CGM (blue; Marcolini et al 2004;Anglés-Alcázar et al 2017a), the growth of magnetic fields (yellow; Hanasz et al 2004;Pakmor et al 2017), metallicityi evolution (cyan; Torrey et al 2018), mergers and merger induced star formation (red; Robertson et al 2006b;Jiang et al 2008;Boylan-Kolchin et al 2008;Hani et al 2020), environmental factors (grey; Mo et al 2010;Lilly et al 2013) and galaxy quenching (pink; Sales et al 2015;Nelson et al 2018b;Wright et al 2019;Rodríguez Montero et al 2019). While the figure shows the large range of estimated timescales for different processes, it also encodes the diversity in the estimated timescales of individual processes (e.g., quenching timescales) across different models in the literature.…”
Section: Take Down Policymentioning
confidence: 99%
“…Mergers: Mergers between galaxies bring in a combination of stars that have already formed and gas that can fuel a burst of subsequent star formation, with timescales ranging from ∼ 100 − 500 Myr (Hernquist 1989;Barnes & Hernquist 1991Mihos & Hernquist 1996;Robertson et al 2006b;Hani et al 2020). The effect on SFHs comes from mergers as a a primary mechanism for driving starbursts in galaxies (in addition to disk instabilities) and as a controversial trigger for quenching, depending on a variety of factors including the mass ratio, relative alignment, how gasrich the merger is, and even if the merger triggers a central AGN (Hopkins et al 2006;Governato et al 2009).…”
Section: The Characteristic Timescales Of Physical Processes In Simulmentioning
confidence: 99%